The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.21276/ijcmr.2018.5.8.13
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin Time (PT) and Activated Partial Thromboplastin Time (APTT) in Type 2 Diabetes Mellitus, a Case Control Study

Abstract: Introduction: Diabetes mellitus (DM) is characterized by hyperglycemia accompanied with the biochemical alterations in carbohydrate, protein and lipid metabolism. Diabetics have been shown to be in procoagulant state due to abnormalities in several plasma proteins in blood coagulation.Measurement of prothrombin time (PT), activated partial thromboplastin time (APTT), bleeding time and clotting factor concentration are usually done in patients with a suspected abnormal coagulation. The present study was planned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
1
8
0
2
Order By: Relevance
“…This study showed no significant difference in all age groups in type 2 diabetics. The findings are similar to the work of Ephraim et al, [24]; Thukral et al, [26] that reported no difference in age in PT level among diabetics. The findings of the study observed elevated level in female T2D which was not statistically significant.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study showed no significant difference in all age groups in type 2 diabetics. The findings are similar to the work of Ephraim et al, [24]; Thukral et al, [26] that reported no difference in age in PT level among diabetics. The findings of the study observed elevated level in female T2D which was not statistically significant.…”
Section: Discussionsupporting
confidence: 91%
“…Abdeen and Hamza et al, [25] observed prolongation of PT due to deficiency of coagulation factors in relation to diabetic duration. Thukral et al, [26] observed higher level of PTin type diabetics which indicated abnormal coagulation mechanism involving tendency of bleeding due to thromboembolic haemorragic disorder. A cross sectional study conducted by Obeagu et al, [27] showed no significant difference in the level of prothrombin time between diabetics and control subjects.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…10 Diabetes considered to be the independent risk factor for the development of atherosclerosis. Therefore, atherosclerosis is the main cause of macrovascular complications, 1,24 and therefore, causes increased platelet activation, activation of coagulation factors, and hypo fibrinolysis significantly associated with an increased risk of cardiovascular disease. 1,[24][25][26] In this study, PT and INR were significantly reduced in T2DM patients as compared to T1DM and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies involved coagulation profiles and platelet parameters among diabetic patient-reported contrasting findings. Some studies reported that normal APTT and PT, 21 , 22 and some other studies reported that significantly prolonged APTT and PT among patients with T2DM 23 , 24 and some other related studies also reported that shortened APTT and PT among T2DM patient. 25 , 26 Activated partial thromboplastin time is a screening test for intrinsic and common pathways of coagulation and PT is a screening test for extrinsic and common pathways of coagulation systems standardized by using INR to normalize for the variable responsiveness of thromboplastin reagents.…”
Section: Introductionmentioning
confidence: 93%